Comparing bioelectrical activity of the peripheral retina among myopic patients operated for rhegmatogenous retinal detachment complicated by choroidal detachment - Alibet Yassine; V.S. Ponomarchuk; G.V. Levytska; N.I. Khramenko (Journal of Ophthalmology, 2018)
Background: High myopia is known to be a major risk factor for the development of choroidal detachment (CD) in eyes with rhegmatogenous retinal detachment (RRD). Trophic disturbances of the retina in axial myopia have been previously confirmed by electroretinography (ERG) data, and are likely to play an important role in the pathogenesis of RRD complicated by CD. To the best of our knowledge, no study has examined in detail the ERG in myopic patients operated for RRD combined with CD.